Prevalence and phylogeny of Chlamydiae and hemotropic mycoplasma species in captive and free-living bats - Janine Fritschi; Hanna Marti; Helena M. B. Seth-Smith; Sébastien Aeby; Gilbert Greub; Marina L. Meli; Regina Hofmann-Lehmann; Kristin Mühldorfer; Nadine Stokar-Regenscheit; Danja Wiederkehr; Paola Pilo; Peggy Rüegg- Van Den Broek; et al. (BMC Microbiology, 2020)
Abstract Background Bats are hosts for a variety of microorganisms, however, little is known about the presence of Chlamydiales and hemotropic mycoplasmas. This study investigated 475 captive and free-living bats from Switzerland, Germany, and Costa Rica for Chlamydiales and hemotropic mycoplasmas by PCR to determine the prevalence and phylogeny of these organisms. Results Screening for Chlamydiales resulted in a total prevalence of 31.4%. Positive samples originated from captive and free-living bats from all three countries. Sequencing of 15 samples allowed the detection of two phylogenetically distinct groups. These groups share sequence identities to Chlamydiaceae, and to Chlamydia-like organisms including Rhabdochlamydiaceae and unclassified Chlamydiales from environmental samples, respectively. PCR analysis for the presence of hemotropic mycoplasmas resulted in a total prevalence of 0.7%, comprising free-living bats from Germany and Costa Rica. Phylogenetic analysis revealed three sequences related to other unidentified mycoplasmas found in vampire bats and Chilean bats. Conclusions Bats can harbor Chlamydiales and hemotropic mycoplasmas and the newly described sequences in this study indicate that the diversity of these bacteria in bats is much larger than previously thought. Both, Chlamydiales and hemotropic mycoplasmas are not restricted to certain bat species or countries and captive and free-living bats can be colonized. In conclusion, bats represent another potential host or vector for novel, previously unidentified, Chlamydiales and hemotropic mycoplasmas.